The impact of tangeretin combined with whey protein supplementation on body composition and hormonal profiles in elite sprinters: A double-blind RCT - Cao, Z.; Zhang, Z.; Liu, M. (Journal of Exercise Science & Fitness, 2026)
Objective This study explored the combined effects of tangeretin and whey protein on serum testosterone and cortisol in competitive athletes. Methods In a double-blind,controlled trial, 24 elite sprinters were divided into two groups: an experimental group (EXP, n = 12) taking tangeretin (200 mg) and whey protein (19.8 g) daily, and a control group (CTRL, n = 12) taking only whey protein (19.8 g) over four weeks. Weekly and post-intervention tests measured serum testosterone, cortisol, superoxide dismutase (SOD) activity, and adrenocorticotropic hormone (ACTH) levels, along with pre- and post-intervention anthropometric assessments. Results After intervention, a significant Time × Group interaction was observed for fat-free mass (FFM), which increased significantly in the EXP but not in the CTRL, with a greater percentage increase in EXP (2.3 % vs. 1.1 %, p = 0.018). Similar interactions were found for fat mass and body fat percentage, which decreased significantly in EXP. For biochemical indicators, no significant Group × Time interactions were found. However, a significant main effect of time was identified for serum testosterone and ACTH, indicating comparable temporal changes in both groups. No significant time or interaction effects were observed for cortisol, T/C ratio and SOD. Conclusion Four weeks of combined whey protein and tangeretin supplementation significantly improved body composition in elite sprinters, whereas it did not significantly alter systemic hormonal profiles or antioxidant activity compared to whey protein alone.